Challenges of Topological Insulator Research: Bi2Te3 Thin Films and Magnetic Heterostructures. Issue 1 (22nd September 2020) - Pereira, Vanda M.; Wu, Chi-Nan; Höfer, Katharina; Choa, Arnold; Knight, Cariad-A.; Swanson, Jesse; Becker, Christoph; Komarek, Alexander C.; Rata, A. Diana; Rößler, Sahana; Wirth, Steffen; Guo, Mengxin; et al.
Abstract : Topological insulators (TIs) are of particular interest in the recent solid‐state research because of their exceptional features stemming from the conducting, topologically protected surface states. The exotic properties include the occurrence of novel quantum phenomena and make them promising materials for spintronics and quantum computing applications. Theoretical studies have provided a vast amount of valuable predictions and proposals, whose experimental observation and implementation, to date, are often hindered by an insufficient sample quality. The effect of even a relatively low concentration of defects can make the access to purely topological surface states impossible. This points out the need of high‐quality bulk‐insulating materials with ultra‐clean surfaces/interfaces, which requires sophisticated sample/device preparations as well as special precautions during the measurements. Herein, the challenging work on 3D TI thin films with a focus on Bi 2 Te 3 is reported. It covers the optimization of the molecular beam epitaxy growth process, the in situ characterization of surface states and transport properties, the influence of exposure to ambient gases and of capping layers, as well as the effect of interfacing TI thin film with magnetic materials. Abstract : As the topologically relevant carrier density in Bi2 Te3 is less than 1% of the surface unit cell, the contribution of charge carriers from topologically trivial states (induced, e.g., by exposure to air) has to be kept extremely small not to mask the topological effects. This feature article reviews the challenges hindering the experimental observation of theoretically predicted phenomena in Bi2 Te3 thin films.